Interspecies Comparison of Platelet Aggregation, LIBS Expression and Clot Retraction: Observed Differences in GPIIb-IIIa Functional Activity - Jennings, Lisa K; White, Melanie M; Mandrell, Timothy D (Thrombosis and Haemostasis, 1995)
We examined interspecies differences in the function of the platelet fibrinogen receptor, GPIIb-IIIa, by comparing platelet aggregation responses to adenosine diphosphate (ADP) added alone or in combination with a GPIIIa specific monoclonal antibody (mAb), D3. D3 can activate the GPIIb-IIIa receptor in the absence of platelet activation, and it preferentially binds to a region on the GPIIIa subunit after the GPIIb-IIIa complex is occupied by ligand. Using human, monkey, dog, rabbit and pig platelets, we examined whether all species’ platelets bound the D3 mAb similarly, and if the binding of Arg-Gly-Asp-Ser (RGDS) peptides induced the exposure of the anti-LIBS (D3) epitope as previously described for human platelets. We also evaluated how blocking of this neoantigenic region by the D3 mAb affected clot retraction, a process that requires linkage of GPIIb-IIIa with fibrin(ogen) and the platelet cytoskeleton. We found that all species tested bound the D3 mAb. Only in human and monkey platelets did D3 cause aggregation as well as inhibit clot retraction. However, in all species tested, except for pig, D3 prevented disaggregation of platelets typically observed when platelets are treated with low dose ADP. With the exception of pig platelets, there was increased D3 binding to platelets in the presence of RGDS peptides. We propose that this region of GPIIIa is important in the conformational changes that GPIIb-IIIa undergoes during the binding of ligand in most species tested. Our studies suggest 1) there are measurable inter-species differences in GPIIb-IIIa mediated platelet aggregation and clot retraction, 2) LIBS expression due to receptor occupancy is a common but not all-inclusive response and 3) interspecies comparisons may be useful in understanding structural and functional aspects of platelet GPIIb-IIIa.